The impact and mechanism of action of the digital economy on agricultural new quality productive forces: a discussion of the threshold effect and spatial spillover effect - Chao Feng; Zhengzhong Jiang; Ying Zhang; Xieqihua Liu; Yi Zhu; Bin Liu; Bin Liu; Bin Liu (Frontiers in Sustainable Food Systems, 2025)
The digital economy is an important driving force for developing agricultural new quality productive forces. This academic is based on panel data from 31 provinces in China from 2012 to 2021. It uses econometric methods such as the two-way fixed effect model, the mediating effect model, the panel threshold model, and the spatial autoregression (SAR) model to empirically study the impact effect and mechanism of action of the digital economy on agricultural new quality productive forces. Research shows that (1) The digital economy significantly promotes agricultural new quality productive forces, and this conclusion is still valid after considering a series of endogenous tests. (2) The digital economy has obvious geographical differences in its effect on generating agricultural new quality productive forces. (3) Agricultural technological progress is an important mechanism through which the digital economy affects the promotion of agricultural new quality productive forces. (4) Further research has found that the digital economy has a ‘promoting-inhibiting-promoting’ nonlinear threshold effect on agricultural new quality productive forces. (5) The digital economy exerts considerable regional spillover effects on agricultural new quality productive forces. This study proposes four recommendations based on the current conclusions. (1) The government should enhance and endorse the advancement of the digital economy while mitigating regional disparities in its development. (2) The local government should expedite the development of digital infrastructure to facilitate the transition from traditional agricultural to digital agriculture. (3) Local governments should contribute to the progression of agricultural technologies. (4) local governments should leverage the spatial spillover effect of the digital economy to facilitate coordinated regional growth.